factorize

xsquared-x-6.

how do u do this?

Printable View

- Jan 13th 2008, 05:17 AMhelp_me[SOLVED] factorising quadratics
factorize

xsquared-x-6.

how do u do this? - Jan 13th 2008, 05:26 AMPeritus
well you can use, the following formula to find theroots of the quadratic equation:

X1 = 0.5*(1 + sqrt(1 + 24)) = 3

X2 = 0.5*(1 - sqrt(1 + 24)) = -2

thus the factorization is: (x-3)*(x+2)

the general fomula for finding the roots of a quadratic equation of the following form:

p(x) = a*x^2 + b*x + c

is:

X1 = (-b + sqrt(b^2 - 4*a*c)) / (2*a)

X2 = (-b - sqrt(b^2 - 4*a*c)) / (2*a)

also notice that if "a" does not equal 1 the factorization will be

a*(x-X1)*(x-X2)